High frequency drain current noise modeling in MOSFETs under sub-threshold condition - Chan, Lye Hock (2010)
A new high frequency drain current noise model was developed for MOSFETs under sub-threshold condition. A simple parameter extraction technique is proposed, which utilizes Y-parameter analysis on the RF small-signal equivalent circuit. Good agreement has been obtained between the predicted and measured results up to 20 GHz.